Management Effectiveness of Educators and Education Personnel - Firmansyah Firmansyah; Muhammad Amin; Endang Komara; Waska Warta (Edumaspul: Jurnal Pendidikan, 2023)
Educator management and education personnel are activities that must be carried out from educators and education personnel entering the educational organization to stopping through the process of HR planning, recruitment, selection, placement, compensation, awards, education and development training, and dismissal. Education and education management must absolutely be applied by the principal in order to utilize Human Resources effectively efficiently to achieve optimal results. The purpose of this study is to know and describe the planning, organizing, and supervision of educators and education personnel. The research approach with qualitative methods, the research was carried out from February to April 2023 at SMAN 18 North Jakarta with the results of the study showing that in general the planning, organization and supervision carried out by employee management at SMAN 18 North Jakarta have been carried out effectively, namely by compiling and implementing work programs from each apparatus or each education staff, Then divide the duties of each education staff according to the abilities they have